Analisis Dampak Sertifikasi Halal terhadap Kepercayaan Konsumen dan Pertumbuhan Ekonomi UMKM - Erizal Candra Efendi; Ruri Mustika; Wildan Hadi (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study examines the impact of halal certification on consumer trust and the economic growth of Micro, Small, and Medium Enterprises (MSMEs) in Padang, Pekanbaru, Medan, and Bengkulu. The research aims to identify how halal certification influences consumer perceptions, loyalty, and the expansion of MSME markets. A qualitative approach was employed, using in-depth interviews and documentation from 32 MSMEs across the four cities. The findings reveal that halal certification significantly enhances consumer trust in product quality, hygiene, and compliance with Islamic principles. Increased trust leads to higher customer loyalty, repeated purchases, and recommendations, which in turn boost MSME revenues and market share. Additionally, MSMEs that actively utilize halal certification in marketing strategies experience greater visibility and opportunities for domestic and international market expansion. Halal certification thus serves not only as a religious compliance requirement but also as a strategic instrument for sustainable economic development of MSMEs. The study contributes to the field of economics and business by demonstrating the practical benefits of certification in enhancing consumer confidence and supporting MSME growth. Keywords: Halal Certification; MSME Growth; Market Expansion; Economic Development